A Communicative Approach to Meaning Discrimination in Bilingual Passive Dictionaries - Gharaei, Zohreh; Moinzadeh, Ahmad (Richtmann Publishing, 2012)
Advances made in the area of linguistics and lexicography have affected the way bilingual dictionaries are perceived. Bilingualdictionaries, as important devices in intercultural and interlingual communications, are not regarded as mere reference tools containing alist of items with their corresponding translation equivalents. Nowadays, the role of the user in lexicographic communication has beenhighlighted and every decision made in the process of dictionary making is based on the purpose the dictionary is going to serve and theintended users' needs and expectations. The present article aims at studying the issue of sense discrimination in bilingual passivedictionaries from a communicative perspective. In so doing, meaning discrimination and its importance is discussed. Then, the factorsinfluencing the application of meaning discrimination strategies are introduced. In addition to equivalent relation which is a factor alreadydiscussed by the scholars of the field, part of speech is introduced by the researchers as the second factor contributing to meaningdiscrimination. It is concluded that the entries having more complicated equivalent relations need more meaning discriminatorystrategies. Besides, verbs, due to the role they have in comprehension and due to their polysemous nature, call for more meaningdiscriminatory strategies.